2021
DOI: 10.3390/genes12101591
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression Profiling of Circulating MicroRNAs in Serum of Cysticercus pisiformis-Infected Rabbits

Abstract: Cysticercus pisiformis (C. pisiformis), the larval form of Taenia pisiformis, parasitize mainly the liver, omentum and mesentery of rabbits and cause huge economic losses in the rabbit breeding industry. MicroRNA (miRNA), a short non-coding RNA, is widely and stably distributed in the plasma and serum. Numerous data demonstrates that, after parasitic infection, miRNAs become the key regulatory factor for controlling host biological processes. However, the roles of serum miRNAs in C. Pisiformis-infected rabbits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Domestic rabbits belonging to the species Oryctolagus cuniculus are social animals and are descended from European animals (Owuor et al, 2019). It is well known that domestic rabbits are intended for meat consumption and are a valuable source of a number of nutrients, but may contain many different endoparasites, including Passalurus ambiguus (Abdel-Gaber et al, 2019), Trichostrongylus retortaeformis (Cattadori et al, 2019), Nematodirus leporis (Tizzani et al, 2020), Cysticercus pisiformis (Chen et al, 2021) and Eimeria spp. (Ladron de Guevara et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Domestic rabbits belonging to the species Oryctolagus cuniculus are social animals and are descended from European animals (Owuor et al, 2019). It is well known that domestic rabbits are intended for meat consumption and are a valuable source of a number of nutrients, but may contain many different endoparasites, including Passalurus ambiguus (Abdel-Gaber et al, 2019), Trichostrongylus retortaeformis (Cattadori et al, 2019), Nematodirus leporis (Tizzani et al, 2020), Cysticercus pisiformis (Chen et al, 2021) and Eimeria spp. (Ladron de Guevara et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, research has identified egr‐miR‐2a‐3p as a potential diagnostic biomarker for cystic echinococcosis (CE) 17 . Previous studies have revealed that cestodes share the same miRNA let‐7 (let‐7‐5p), 18 which has been shown to be one of the highly expressed miRNAs in cestodes 19‐21 . In addition, the expression level of let‐7‐5p was significantly upregulated in the serum and liver of metacestodes‐infected animals and humans, 22‐24 suggesting its potential as a target molecule for diagnosing metacestodiasis.…”
Section: Introductionmentioning
confidence: 99%
“…Cysticercus pisiformis is a widely prevalent larval form of tapeworm that primarily parasitizes the liver, omentum, and mesenteries of lagomorphs and rodents, leading to the development of cysticercosis pisiformis ( 1 , 2 ). Among these hosts, rabbits are the most frequently affected and suffer significant consequences from cysticercosis pisiformis.…”
Section: Introductionmentioning
confidence: 99%